Efficacy and safety of 12 immunosuppressive agents for idiopathic membranous nephropathy in adults: A pairwise and network meta-analysis - Liu, Jiarong; Li, Xiang; Huang, Tianlun; Xu, Gaosi (Frontiers in Pharmacology, 2022)
Abstract Background: Immunosuppressants have been applied in the remedy of idiopathic membranous nephropathy (IMN) extensively. Nevertheless, the efficacy and safety of immunosuppressants don’t have final conclusion. Thus, a pairwise and network meta-analysis (NMA) was carried out to seek the most recommended therapeutic schedule for patients with IMN. Methods: Randomized controlled trials (RCTs) including cyclophosphamide (CTX), mycophenolate mofetil (MMF), tacrolimus combined mycophenolate mofetil (TAC+MMF), cyclosporine (CsA), tacrolimus (TAC), leflunomide (LEF), chlorambucil (CH), azathioprine (AZA), adrenocorticotropic hormone (ACTH), non-immunosuppressive therapies (CON), steroids (STE), mizoribine (MZB) and rituximab (RIT) for patients with IMN were checked. Risk ratios (RRs) and standard mean difference (SMD) were reckoned to assess dichotomous variable quantities and continuous variable quantities, respectively. Total remission (TR) and 24 hours urine total protein (24h UTP) were compared using pairwise and NMA. And then interventions were ranked on the basis of the surface under the cumulative ranking curve (SUCRA). Results: Our study finally included 51 RCTs and 12 different immunosuppressants. compared with CON group, most regimens demonstrated better therapeutic effect in TR, with RRs of 2.1 (95% CI) (1.5 to 2.9) for TAC, 1.9 (1.3 to 2.8) for RIT, 2.5 (1.2 to 5.2) for TAC+MMF, 1.9 (1.4 to 2.7) for CH, 1.8 (1.4 to 2.4) for CTX, 2.2 (1.0 to 4.7) for ACTH, 1.6 (1.2 to 2.1) for CsA, 1.6 (1.0 to 2.5) for LEF and 1.6 (1.1 to 2.2) for MMF. In terms of 24h UTP, TAC (SMD, −2.3 (95% CI −3.5 to −1.1)), CTX (SMD, −1.7 (95% CI −2.8 to −0.59)), RIT (SMD, −1.8 (95% CI −3.5 to −0.11)), CH (SMD, −2.4 (95% CI −4.3 to -0.49)), AZA (SMD, −-4.2 (95% CI −7.7 to -0.68)) and CsA (SMD, −1.7 (95% CI −3 to -0.49)) could significantly superior than the CON group. Conclusions: This study indicates that TAC+MMF performed the best in terms of TR and TAC shows the best effectiveness on 24h UTP compared with other regimens. On the contrary, there seems to be little advantage on STE alone, LEF, AZA and MZB in treating patients with IMN compared with CON.